IMPLEMENTASI SISTEM INFORMASI GEREJA BERBASIS WEB UNTUK MENDUKUNG MANAJEMEN DAN PELAYANAN JEMAAT GKJ SEMARANG TIMUR - Yustisnias, Xavier Cahaya; Dharmawan, Alexander; Yusup, Yusup (LPPM Politeknik Saint Paul Sorong, 2025)
The Gereja Kristen Jawa (GKJ) Semarang Timur is located in the East Semarang area, with approximately 350 registered members, though average weekly worship attendance is only around 100 people. Member data is still recorded manually in printed books, while information on church activities, offerings, finances, inventory, and other updates is shared through WhatsApp groups or the printed Church Bulletin, which is only distributed during Sunday services. This limits access for members who are absent and makes data recording and retrieval inefficient. This study aims to design and develop a web-based information system to facilitate member data management, dissemination of worship information, and provide a platform for members to evaluate church services. The system includes features for member records (including transfers and deaths), event schedule management, evaluation forms, and regularly updated announcements. The system design follows the waterfall method, with data collected through observation, interviews, and literature review. Primary data was obtained from the GKJ Semarang Timur Church Council and administrative staff, while secondary data came from journals and books related to web-based information system development. The resulting website features a simple, user-friendly interface tailored to the church administration’s needs. The implementation of this system is expected to improve data search efficiency, expand the reach of church information, and serve as an effective communication medium between the church and its members. its congregation.